A human fibrosarcoma inhibits systemic angiogenesis and the growth of experimental metastases via thrombospondin-1 - Volpert, Olga V. (The National Academy of Sciences, 1998)
Concomitant tumor resistance refers to the ability of some large primary tumors to hold smaller tumors in check, preventing their progressive growth. Here, we demonstrate this phenomenon with a human tumor growing in a nude mouse and show that it is caused by secretion by the tumor of the inhibitor of angiogenesis, thrombospondin-1. When growing subcutaneously, the human fibrosarcoma line HT1080 induced concomitant tumor resistance, preventing the growth of experimental B16/F10 melanoma metastases in the lung. Resistance was due to the production by the tumor cells themselves of high levels of thrombospondin-1, which was present at inhibitory levels in the plasma of tumor-bearing animals who become unable to mount an angiogenic response in their corneas. Animals carrying tumors formed by antisense-derived subclones of HT1080 that secreted low or no thrombospondin had weak or no ability to control the growth of lung metastases. Although purified human platelet thrombospondin-1 had no effect on the growth of melanoma cells in vitro, when injected into mice it was able to halt the growth of their experimental metastases, providing clear evidence of the efficacy of thrombospondin-1 as an anti-tumor agent.